Role of Employee Well-Being Mediating Psychological Empowerment and Perceived Organizational Support on Teacher Organizational Citizenship Behavior - Isnaenti Nur Latifah; Jaya Addin Linando (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Organisational Citizenship Behaviour (OCB) among teachers is an important factor in enhancing the effectiveness and quality of school performance. Various factors, including psychological empowerment and perceived organisational support, can influence OCB. In addition, employee well-being also plays a significant role in fostering positive behaviour among teachers in the workplace. Therefore, this study aims to analyse the role of employee well-being in mediating the effects of psychological empowerment and perceived organisational support on organisational citizenship behaviour among teachers. This study employed a quantitative approach using a survey method. Data were collected via questionnaires using a Likert scale, distributed to teachers as research respondents, yielding a total of 199 teacher respondents in Indonesia. The data analysis techniques included instrument testing, classical assumption tests, regression analysis, and hypothesis testing to determine both direct and indirect effects among the research variables. The results showed that psychological empowerment and perceived organisational support have positive and significant effects on organisational citizenship behaviourr, and both variables also have positive and significanteffectst on employee well-being. Furthermore, employee well-being has a positive and significant effect on organisational citizenship behaviour. The analysis also indicates that employee well-being can mediate the effects of psychological empowerment and perceived organisational support on organisational citizenship behaviour. Enhancing psychological empowerment and perceived organisational support among teachers can improve their well-being, which in turn encourages the emergence of organisational citizenship behaviour.